2022
DOI: 10.12688/f1000research.123591.1
|View full text |Cite
|
Sign up to set email alerts
|

Squalomix: shark and ray genome analysis consortium and its data sharing platform

Abstract: The taxon Elasmobranchii (sharks and rays) contains one of the long-established evolutionary lineages of vertebrates with a tantalizing collection of species occupying critical aquatic habitats. To overcome the current limitation in molecular resources, we launched the Squalomix Consortium in 2020 to promote a genome-wide array of molecular approaches, specifically targeting shark and ray species. Among the various bottlenecks in working with elasmobranchs are their elusiveness and low fecundity as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…A shortcoming of this study is that relatively few tissue transcriptomes were available to us, and therefore a less than optimal genome annotation was possible; nonetheless, the preliminary annotation deposited on dryad is likely to be of benefit to other researchers. The extreme divergence times of elasmobranchs relative to other vertebrates, as well as a paucity of other chromosome-level sequences from this sub-class, also hamper thorough annotations, an aspect likely soon to be at least partially alleviated with the publication of additional shark species genomes currently in the VGP and Squalomix Consortium 50 pipelines. Another limitation of our study is that the heterozygosity and FROH values we report here for great hammerhead, although concerning, arise from a single individual.…”
Section: Discussionmentioning
confidence: 99%
“…A shortcoming of this study is that relatively few tissue transcriptomes were available to us, and therefore a less than optimal genome annotation was possible; nonetheless, the preliminary annotation deposited on dryad is likely to be of benefit to other researchers. The extreme divergence times of elasmobranchs relative to other vertebrates, as well as a paucity of other chromosome-level sequences from this sub-class, also hamper thorough annotations, an aspect likely soon to be at least partially alleviated with the publication of additional shark species genomes currently in the VGP and Squalomix Consortium 50 pipelines. Another limitation of our study is that the heterozygosity and FROH values we report here for great hammerhead, although concerning, arise from a single individual.…”
Section: Discussionmentioning
confidence: 99%
“…The first PCR was performed at multiple annealing temperatures to identify a condition that gives a single- or near single-band product on agarose gel. We performed Sanger sequencing to confirm the identity of the nucleotide sequence of the first PCR product to the sequence from the transcriptome assembly which was obtained from the Squalomix sequence archive 28 . We also confirmed that qPCR primers (to be used for genome size estimation) do not overlap heterozygous polymorphic sites inside the DNA standard sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Orthologs of those CVGs of the target species were identified by performing BLAST (TBLASTN) search in transcriptome assemblies of the target species in the Squalomix elasmobranch sequence archive (https://github.com/Squalomix/sequences; ref. 28 ), using amino acid sequences of human CVG orthologs as the query. Also, the deduced amino acid sequences of the longest open reading frame of the identified transcripts were used for the BLAST (BLASTP) search against the human protein database.…”
Section: Selection Of Reference Genes and Primer Designmentioning
confidence: 99%
“…Standardized genome size C-values (haploid DNA content per cell measured in picograms, pg/n) were collected from the Animal Genome Size Database (Release 2.0) 31 , the Squalomix consortium data repository 14 , 32 , 33 , and the literature 7 , 13 , 34 (and references therein), excluding values from potential triploid cytotypes or hypertrophic cells. Measurement technique was shown not to significantly influence species-specific genome size estimations across vertebrates (mixed-effects ANOVA [fixed effect: measurement technique; random effect: species]: F = 0.65, p = 0.597, n estimates = 20, n groups = 5; R package nlme v. 3.1.164 35 ; data from the Animal Genome Size Database).…”
Section: Methodsmentioning
confidence: 99%